The issuer and investor credit ratings – the impact on the stock prices - Chodnicka-Jaworska, Patrycja (Research Papers of Wrocław University of Economics, 2018)
The basic goal of the article is to analyse the impact of credit rating changes on the rates of return on banks’ shares, considering the entity that asked for assigning a credit rating. The following hypotheses are proposed: banks’ share prices react stronger to the investor-paid credit rating changes. the strongest impact of the banks’ credit rating changes is observed for a downgrade, for both the issuer and the investor credit ratings, while a stronger significant reaction is observed after the moment of publication. The analysis was prepared on the Thomson Reuters Database. The analysis was carried out on data from the years 1980 to 2015, for banks from the European countries, by using event study methods
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 519, s. 40-52
Keywords: credit rating; issuer; investor; stock prices; event study; emitent; inwestor; kursy akcji